Correlation between CT and operative findings in pancreatic cancers and role of pre-operative CA19-9 values in predicting metastatic disease - Prabhakar, Rajat; Jaiswal, Shyam S.; Prakash, Ravi (International Surgery Journal, 2021)
Background: Pancreatic cancers carry a poor prognosis with 20-30% of cases found resectable on MDCT (Multi-detector CT). 60-91% of these lesions are actually found resectable during surgery. CA 19-9 is an extensively studied tumour marker in pancreatic cancers and its abnormally high value may point towards metastatic disease. Methods: A study was conducted in a tertiary care centre in which all patients of pancreatic cancers found resectable on imaging were subjected to surgery after staging laparoscopy to find metastatic disease missed on MDCT, the findings were noted and correlated with the radiological findings. Also, pre-operative CA 19-9 levels were analysed to predict metastatic disease in patients with high CA 19-9 values. Results: The study included 34 patients of pancreatic cancers deemed resectable on imaging. Out of these, four (11.7%) patients were found to be unresectable on staging laparoscopy in the form of subcentimetric liver/peritoneal metastasis. It was also found that preoperative CA 19-9 levels were higher in patients found to be metastatic. By using ROC curve, it was found that pre-operative values of CA 19-9 had 100% sensitivity and 80% specificity at the cut off level >106.75 U/ml. Conclusions: MDCT fails to identify some unresectable diseases because of presence of distant metastasis in the form of liver and peritoneal metastatic nodules and malignant ascites. Staging laparoscopy prior to laparotomy is a useful procedure which prevents unwanted laparotomy in some cases of metastatic pancreatic cancer not identified on imaging. Abnormally high values of CA 19-9 may point towards metastatic disease.